El litigio ambiental ante la Corte Centroamericana de Justicia - Kahl, Sonja (2026)
This article analyzes possibilities of environmental litigation before the Central American Court of Justice. It first analyzes the Court’s procedural features and environment-related jurisprudence, with a special focus on the San Juan River case. Secondly, the paper explores environmental litigation before other courts of regional integration in Europe, Africa, and Latin America. It presents some illustrative judgments in order to emphasize the potential of environmental litigation based on regional community law. Finally, the article will highlight some obstacles to environmental litigation before the Central American Court of Justice.